Surface entrapment of chitosan on 3D printed polylactic acid scaffold and its biomimetic growth of hydroxyapatite - Jian, Wang; Zakaria, Nor Hidayah; Abd Razak, Saiful Izwan; Abdul Kadir, Mohammed Rafiq; Mat Nayan, Nadirul Hasraf; Li, Yi; Mat Amin, Khairul Anuar (Taylor & Francis Group, 2018)
This work reports the surface modification of 3D printed PLA scaffold with chitosan and its hydroxyapatite (HA) forming capability. PLA scaffold was fabricated using a desktop 3D printer followed by the inclusion of chitosan on the surface via surface entrapment. Confocal laser scanning microscopy (CLSM) images showed existence of chitosan entrapment with depth of 24 μm. Immersion of the modified PLA scaffold in simulated body fluid resulted in formation of apatite layers on the surface. Plus the entrapment method does not induce any cytotoxic response towards human fibroblast cell. This method provides a facile approach of obtaining 3D printed scaffold with good bioactivity thus has potential in biomimetic and tissue engineering.